1987
DOI: 10.1016/s0010-0277(87)80006-9
|View full text |Cite
|
Sign up to set email alerts
|

Do six-month-old infants perceive causality?

Abstract: The idea of cause and effect is often assumed to originate in prolonged learning. However, the present findings suggest that 27-week-old infants may already perceive a cause-effect relationship. Reversal of an apparently causal event (direct launching) produced more recovery of attention following habituation than the reversal of a similar but apparently non-causal event (delayed reaction). In both cases the changes in the spatiotemporal properties of the stimuli were identical. Hence the infant's percept of d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
524
3
5

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 924 publications
(550 citation statements)
references
References 21 publications
18
524
3
5
Order By: Relevance
“…A large body of work indicates that prelinguistic infants and toddlers can identify thematic role related concepts. Causality (Leslie & Keeble, 1987) and intentionality (Behne, Carpenter & Tomasello, 2005) are useful for identifying agents, object motion (Spelke, 1990) is useful for themes, and goaldirected behaviour (Woodward, 1998) signals locations. Even syntactic bootstrapping studies, which are often used to emphasise the difficulty in inferring meaning situationally, provide some evidence for the ability to infer relational meaning such as thematic roles, otherwise children would not be able to look appropriately at a matching causative or non-causative video even for familiar verbs.…”
Section: Discussionmentioning
confidence: 99%
“…A large body of work indicates that prelinguistic infants and toddlers can identify thematic role related concepts. Causality (Leslie & Keeble, 1987) and intentionality (Behne, Carpenter & Tomasello, 2005) are useful for identifying agents, object motion (Spelke, 1990) is useful for themes, and goaldirected behaviour (Woodward, 1998) signals locations. Even syntactic bootstrapping studies, which are often used to emphasise the difficulty in inferring meaning situationally, provide some evidence for the ability to infer relational meaning such as thematic roles, otherwise children would not be able to look appropriately at a matching causative or non-causative video even for familiar verbs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, although there are no familiar content words in the sentence The blicket daxed the wug to the blorg, adults can infer that the event involved transfer and that dax means something kind of like give (Gilette, Gleitman, Gleitman, & Lederer, 1999;Kako, 2006;Snedeker & Gleitman, 2004 There is rich body of evidence showing that basic spatial and temporal cues play a critical role in distinguishing a causal event from a noncausal one (Leslie & Keeble, 1987;Leslie, 1984;Michotte, 1963;Muentener & Carey, 2010). This kind of causal perception has primarily been studied using simple motion events with two sub-events (e.g., one billiard ball rolling, and then another one rolling).…”
Section: Linking Language and Eventsmentioning
confidence: 99%
“…There is rich body of evidence showing that basic spatial and temporal cues play a critical role in distinguishing a causal event from a noncausal one (Leslie & Keeble, 1987;Leslie, 1984;Michotte, 1963;Muentener & Carey, 2010). This kind of causal perception has primarily been studied using simple motion events with two sub-events (e.g., one billiard ball rolling, and then another one rolling).…”
Section: Linking Language and Events: Spatiotemporal Cues Drive Childmentioning
confidence: 99%
See 1 more Smart Citation
“…Some authors have suggested that the perception of causality may even be served by a specialized cognitive module (Leslie & Keeble, 1987;Scholl & Nakayama, 2002).…”
mentioning
confidence: 99%